A cross-sectional study to assess the barriers to teleconsultations among doctors in Chennai - Nagarathinam, Supraja; Umadevi, R.; Grace G, Angeline; Saravanan, Raghul (Journal of Applied Pharmaceutical Research, 2024)
Background: A doctor's communication and interpersonal skills encompass gathering information to facilitate accurate diagnosis, counsel appropriately, give therapeutic instructions, and establish caring relationships with patients. While face-to-face consultations have been the norm, tele-consultations and enrolment in telemedicine apps have become necessary. Tele-consultations have been on the rise significantly during the COVID-19 lockdown. This study aims to assess the barriers to tele-consultations among doctors in Chennai. Methodology: This study uses a cross-sectional design to assess the barriers to tele-consultations among doctors in Chennai using a convenience sampling technique. Data was entered in Microsoft Excel and analyzed using SPSS software version 23. Results: 81.6% of the participants feel that teleconsultations have reduced face-to-face consultations. Only about 6% of the study participants preferred teleconsultation in the future. About a third of the doctors in the study could not treat/manage chronically ill patients through teleconsultations. About 70% of the doctors could follow up with their patients through telecommunication, but 70% failed to follow up. Conclusion: From this study, we conclude that only about 6% of the study participants would prefer teleconsultation in the future. Treating medical emergencies and assessment of surgical patients were considered as top 2 important barriers in this study with about half of them facing this barrier during their telecommunication.